Devil's breath [large type] : a Max Tudor mystery - Malliet, G. M., 1951- (Malliet, G. M., 1951- Max Tudor novel., 2017)
When spy-turned-cleric Max Tudor's former life caught up with him, he obtained his bishop's permission to offer his services to MI5 on an as-needed basis. In Devil's Breath, it's time for him to follow through. The body of a glamorous film star has washed ashore from a luxury yacht, and Max's former colleague wants his help to find the murderer.